Analisis Materi Ajar Pendidikan Agama Islam Dan Budi Pekerti Sekolah Dasar Kelas IV Perspektif HOTS - Romadona, Amalia; Abdurrahman, Maman (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2023)
Islamic religious and ethical education plays an important role in shaping the character of primary school students. To achieve this goal, it’s important to ensure that the material taught in textbooks covers higher cognitive aspects, called higher order thinking skills (HOTS). The purpose of this study is to analyse Islamic religious education and morals textbook for grade 4 elementary school students from the HOTS perspective. The research method used a qualitative approach with document analysis techniques. General textbook used to study Islamic religious teachings and practices for elementary school students were identified and analysed. The focus of the analysis was to find activities that encourage students to think critically, analyse, evaluate and create. The results of the analysis showed that most of the contents of the textbook studied were still not fully in line with the application of HOTS for grade 4 students. Although some questions require general thinking, the proportion of questions is still limited. In addition, some aspects of HOTS such as analysis and evaluation are often not emphasized in the textbook studied. The recommendations of this study can be used by textbook writers, teachers, and education stakeholders to design textbooks that more effectively promote HOTS among students.